-18u-18=-2u-12

Simple and best practice solution for -18u-18=-2u-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18u-18=-2u-12 equation:



-18u-18=-2u-12
We move all terms to the left:
-18u-18-(-2u-12)=0
We get rid of parentheses
-18u+2u+12-18=0
We add all the numbers together, and all the variables
-16u-6=0
We move all terms containing u to the left, all other terms to the right
-16u=6
u=6/-16
u=-3/8

See similar equations:

| 4(-4+x)=5x+1/4 | | 3x+5+5x-18=90 | | m-6=-11+2m | | 8b+28=-4+4b+12 | | √-8+6x=x | | (2/3)z=41/4 | | -7=2x=-45x | | 6=((2/3)x) | | 7n+12=(-23) | | g=19-21 | | √8-6x=x | | 243=27t | | 16n+-16=4n+2 | | 4=6+f | | 0=((2/3)x)-6 | | -7=2x+-4=5x | | (x-4)+x=150 | | -7x+5=8x-25+ | | 3/2=6/((x-3)^2) | | -9x+11-x-2x-33=122 | | 48+2x=x2 | | 4.9+1.3n=1.65 | | x+12/6=7 | | 60/2x=8 | | (2x+1)/3+2=x | | 6=-9x-12 | | 8j-9-3j=+2 | | 17-t=23 | | (1/x-3)-(2/x+1)=(8/x^2-2x-3) | | -6(4x+1)=5-1x | | 10x+5+2x+3x=30 | | X2-12x+35=0 |

Equations solver categories